The Role of Self-Efficacy in Expatriate Adjustment: An Allegorical Perspective: English (Canada) - Cooper, Roseanne D. (Canadian Journal of Counselling and Psychotherapy, 2021)
This paper is unique among the articles written about expatriates in that it focuses on the importance of self-efficacy, on developing one’s cultural identity consciously, and on community building in order to facilitate adjustment. Well-adjusted expatriates build an array of strategies to overcome the many challenges they are faced with: awakening, overwhelmingness, culture shock, grief, uncertainty, communication issues, and identity loss. Most expatriates have had a wide array of experiences and thus can relate to characters with otherworldly experiences. James and the Giant Peach, a remarkable story by Roald Dahl, is used as a platform to illuminate the research literature as an invitation to reconceptualize expatriate adjustment creatively.